2016
DOI: 10.1515/rjim-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection, Gastric Cancer and Gastropanel

Abstract: Gastric cancer (GC) is one of the most widespread types of cancer worldwide. Helicobacter pylori infection has been clearly correlated with gastric carcinogenesis. At present and in the near future, the most important challenge is and will be the significant reduction of mortality due to GC. That goal can be achieved through the identification of higher-risk patients, such as those with atrophic gastritis, intestinal metaplasia and dysplasia. In this review we intend to discuss the importance of diagnosing H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
1
18
0
6
Order By: Relevance
“…[ 75 ] During this process, H. pylori antibody and serum PG concentration showed significant changes, which can be used for risk stratification of gastric cancer in clinic. [ 76 77 78 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 75 ] During this process, H. pylori antibody and serum PG concentration showed significant changes, which can be used for risk stratification of gastric cancer in clinic. [ 76 77 78 ]…”
Section: Discussionmentioning
confidence: 99%
“…PG 1 is produced in the corpus and its levels are reduced in corpus atrophy. When the corpus is inflamed without glandular loss, levels of PG 1 in blood increase [20]. PG 2 is produced in the corpus, antrum and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) generates a heavy disease burden in China. Helicobacter pylori ( H. pylori ) infection is known to play a role in the pathogenesis in most patients with GC . Accumulating evidence has shown that H. pylori infection causes almost 90% of non‐cardiac GC .…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infection is known to play a role in the pathogenesis in most patients with GC. 1 Accumulating evidence has shown that H. pylori infection causes almost 90% of non-cardiac GC. 2 Therefore, a successful eradication of H. pylori would significantly decrease the incidence of GC.…”
Section: Introductionmentioning
confidence: 99%